Protocol for the fast isolation and identification of insecticidal Bacillus thuringiensis strains from soil - Palma, Leopoldo (2015)
Bacillus thuringiensis (Bt) is an ubiquitous, Gram-positive and sporulating bacterium that synthesizes insecticidal proteins with specificity against a wide range of insects during sporulation (Cry and Cyt) and vegetative growth (Vip and Sip). These proteins have portrayed Bt as an environment-friendly alternative to chemical insecticides. However, the intensive use of this resource has promoted the evolution of insect resistance to some of the most used Bt strains to date. Continuous efforts are needed to obtain novel strains exhibiting new specificities in order to overcome insect resistance and maintaining the insecticidal potential of this bacterium. In this work, an experimental procedure for the fast isolation and identification of insecticidal Bt strains is described.